Evaluation of Contemporary Art in the Process of Production, Distribution and Consumption - Alisa Romanovna Lopatkova (Интеракция. Интервью. Интерпретация)
How does the art community evaluate contemporary art? This question is discussed based on 16 interviews with artists, gallery owners, curators, and collectors. The contemporary art market is conceptualized as a “creative industry that unites actors involved in the production, distribution, and consumption of art objects. The research methodology is based on the anthropological approach of Igor Kopytoff and the discursive psychology of Rom Harr?, according to which the history of the movement of cultural objects through social space and the discourses accompanying them are sources of symbolic values. Market practices of art distribution are described: criteria for selecting artists by galleries, legal aspects of distribution and consumption of art objects, informal purchasing practices, moral and pragmatic taboos on buying art objects. Four logics of justifying the value of art objects — “commercial success,” “testimony of the times,” “intellectual development,” “emotional experience”—have been reconstructed. It is demonstrated that consumption as a collector's practice requires following the rules of a “professional approach” to be recognized in the art community.